Sobre Villiers de l'Isle-Adam e seus contos cruéis - Domingos, Norma [UNESP] (My University, 2010)
Villiers de l’Isle-Adam (1838-1889) is always remembered and admired for his books: Contes cruels, L’Ève future and Claire Lenoir- which summarize the main worries of the writer, his satire of the triumphant Positivism, his metaphysical theory and his aspiration for the Ideal. He is one of the greatest artisans of the French literature style of the XIX century and, in spite of some individual and particular characteristics, he shares with other writers from his time – Joris-Karl Huysmans, Barbey d’Aurevilly, Leon Bloy, among others – the same sorrow and fury towards Positivism and Mercantilism. Having as a starting point the collection Contes cruels, the purpose of this article is to reveal the author’s writings who, by searching for the Ideal and by taking refuge in art, is able to unite the poet, the ironic and the idealist philosopher. Through his writings, the writer moves away from the world’s mediocrity and can express a mix of revolt, reaction, rebellion and also, his hopes expressed in his beliefs in the “Au-delà” and in the salvation by the Ideal.

Villiers de l’Isle-Adam (1838-1889) é sempre lembrado e reverenciado por suas três grandes obras – Contes cruels, L’Ève future e Claire Lenoir – que sintetizam as preocupações maiores do autor, ou seja, sua sátira do Positivismo triunfante, sua teoria metafísica e sua aspiração pelo Ideal. Ele é um dos grandes artesãos do estilo da literatura francesa do século XIX e, a despeito de algumas características individuais e particulares, compartilha com autores de sua época – Joris-Karl Huysmans, Barbey d’Aurevilly, Leon Bloy, entre outros – o mesmo desgosto e fúria para com o Positivismo e o mercantilismo. É a partir da coletânea Contes cruels que, neste artigo, procuramos revelar a escritura do autor a qual, em sua busca pelo Ideal, refugiando-se na Arte, consegue reunir o poeta, o ironista e o fi lósofo idealista. Pela escritura, ele afasta-se da mediocridade do mundo e consegue exprimir um misto de revolta, reação, rebelião e, também, esperança, expressa em sua crença no “Au-delà” e na salvação pelo Ideal.
Villiers de l’isle-adam and his cruel short stories
Keywords: Villiers de l’Isle-Adam; Contes cruels; Symbolism; Poetic prose; Fantastic; Irony; Villiers de l’Isle-Adam; Contes cruels; Simbolismo; Prosa poética; Fantástico; Ironia